Fórmula de valoração racional (RVF) e variabilidade no tempo das taxas de retorno de ativos no Brasil - Ripamonti, Alexandre (2011)
Rational valuation formula and time varying cointegration are the main thesis´ concepts, under the Muth´s (MUTH, 1961) rational expectations and theory of price movements as underlying theory, and also testing the null of time invariant error correction mechanisms and another one of inequality of fundamental value and share´s price. The data were obtained from Brazilian listed companies for 1986 to 2010 and also from 1871 to 2010 US stock market. The Johansen´s maximum likelihood and trace models, combined to Chebyshev time polynomials, as proposed by Bierens and Martins (2010) were used in order to test the null. The finds have shown first null rejection and no rejection for the second null. These finds are consistent to Bierens e Martins (BIERENS e MARTINS, 2010) and non-consistent with Muth (MUTH, 1961)